(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
The research aimed to identify the concept of data journalism, and to identify the attitudes of Syrian journalists working in Tishreen newspaper towards data journalism. The research relied on the descriptive-survey approach, and the research sample consisted of (48) male and female journalists from the Syrian journalists working in Tishreen newspaper. A questionnaire consisting of (40) items distributed over four sub-axes was applied to them, and the following statistical methods were applied to extract the results: (percentage, arithmetic mean, and standard deviation). The research concluded with the following results: (percentage, arithmetic mean, and standard deviation). The research concluded with the following results: The level of attitudes of Syrian journalists working in the Syrian Al-Watan newspaper towards data journalism was high, as the arithmetic mean of the research sample members’ response was (3.97). The journalists, members of the research sample, confirmed that they believe that the information contained in data journalism is truthful and that the information contained therein is not boring and repetitive. In light of the research results, the most prominent proposals were: working on providing training courses for Syrian journalists to increase their efficiency in analyzing data and information, how to provide limited data and the possibility of accessing it, and methods of creating the technical infrastructure for news websites.